Effect based monitoring of seasonal ambient air exposures in Australia sampled by PUF passive air samplers - Kennedy, Karen (2010)
There has been relatively little bioanalytical effect based monitoring conducted using samples derived from polyurethane foam (PUF) passive air samplers. Combining these techniques may provide a more convenient and cost effective means of monitoring the potential for biological effects resulting from exposure to complex mixtures in a range of scenarios. Seasonal polycyclic aromatic hydrocarbon (PAH) levels were monitored at sites around Australia using direct chemical analysis. In addition, both indirect acting genotoxicity (umuC assay) and aryl hydrocarbon receptor (AhR) activity (chemically activated fluorescent gene expression [CAFLUX assay]), which are effects potentially relevant to subsequent carcinogenesis for these compounds, were measured. The levels of PAHs as well as genotoxicity and AhR activity were all higher in winter compared to summer and for sites in urban capital cities compared to other locations. Statistically significant relationships were found between the levels of PAHs and both genotoxicity and AhR activity. The dominant contributors to the total AhR activity, were found to be for compounds which are not resistant to H(2)SO(4)/silica gel treatment and were relatively rapidly metabolised that is consistent with a PAH type response. Relative potency estimates for individual PAHs determined for the first time on the CAFLUX assay were used to estimate the proportion of total AhR activity (≤ 3.0%) accounted by PAHs monitored. Observed responses are thus largely due to non-quantified AhR active compounds.